People’s Likes Analysis to Read Crime News (Phenomenological Study on Instagram @kupas_lampung) - Valloma, Fernando; Waskito, Budhi; Poyo, M. (Indonesian Journal Publisher, 2025)
The purpose of this study was to determine the factors that influence public interest in crime news on the Instagram social media platform @kupas_lampung, to determine the impact of crime news on the views, attitudes and actions of Instagram followers @kupas_lampung in everyday life, and to determine how to package crime news that should be presented on the Instagram social media platform @kupas_lampung. The research method used in this study is a qualitative method with a phenomenological approach, which means an approach by studying the direct experiences of the followers of the Instagram account @kupas_lampung. The results of the study show that public interest in crime news on Instagram @kupas_lampung is influenced by the need for up-to-date and accurate information about security. The presentation of news that is short, clear, and equipped with visuals attracts users' attention, despite concerns about sensationalism. This news has an impact on the views and actions of followers, making them more aware and vigilant about security, and encouraging social interactions that increase collective awareness. Therefore, news packaging should prioritize clarity, accuracy, and the use of relevant visuals, with simple language and attention to the protection of victim privacy.